Nexus of urinary tract infection prevalence of the causal organism and predisposing factors in Kanyakine Hospital, Meru, Kenya - Muthee, Irene; Gitonga, Eliphas; Musau, Joseph (International Journal Of Community Medicine And Public Health, 2022)
Background: Globally, urinary tract infection (UTI) is most common during pregnancy, prevalence and incidences being higher than in non-pregnant and elderly women. Inadequate data and information deter UTI prevention and management. Methods: The study targeted UTI positive gravid women seeking antenatal services at Kanyakine hospital. The study assessed history of UTI, lifestyle and hygiene factors. Laboratory test and analysis were conducted on urine specimen collected from 135 randomly sampled study subjects. A semi-structured questionnaire was administered to the sampled subjects and their urine tested to detect presence of microorganisms. The results were analysed using established quantitative methods. Results: Most (47%) of the respondents were Escherichia coli infected while Staphylococcus aureus was detected in 20%. of respondents. Increased rate of sexual intercourse was linked to detection of Escherichia coli in 47.6%, Klebsiella pneumoniae in 40% and yeast (Candida) in 47.4%. Wearing non-cotton undergarment was attributed to detection of E. coli in 68.3%, yeast (63.2%) and Klebsiella pneumoniae (60%) of the respondents. Reduced frequency of changing undergarment led to detection of high pathogen levels. The mode of wiping and type of toilet significantly influenced infection (p˂0.05). Conclusions: Hygiene factors that increases chances of E. coli infection remains among the most significant cause of UTI in gravid mothers. This study recommends integration of an elaborate awareness creation on UTI prevention measures at the early stages of pregnancy and further studies to determine the national UTI burden to device mitigation strategies.